Exit-voice dynamics and the collapse of East Germany the crisis of Leninism and the revolution of 1989 - Pfaff, Steven 1970- (Duke University Press, 2006)
Exit-voice dynamics and collective action -- Blocked voice, demobilization, and the crisis of East German communism -- No exit : the niche society and the limits of coercive surveillance -- Dona nobis pacem : political subcultures, the church, and the birth of dissident voice -- Triggering insurgent voice : the exiting crisis and the rebellion against communism -- Fight or flight? : a statistical evaluation of exit-voice dynamics in the East German revolution -- Why was there no "Chinese solution" in the GDR? -- Activists of the first hour : new forum and the mobilization of reformist voice -- Reunification as the collective exit from socialism